Length-girth relationships of 24 marine fishes in the northern Aegean Sea (eastern Mediterranean Sea) - Adamidou, Angeliki (Array, 2021)
The knowledge of morphological relationships and particularly of those concerning fish body girth (G) with total length (TL) is necessary in gear selectivity and specifically the technical measures to avoid capture of undersized individuals. This study concerns 24 marine species exploited by the small-scale coastal fleet in the Aegean Sea (eastern Mediterranean Sea), for 6 of which, the TL-G relationships are mentioned for the first time in the Mediterranean Sea and the adjacent seas. Samples were collected seasonally, from April 2016 to February 2017. The coefficients of the linear regression of body girth in three body positions, (Geye, posterior to the eye; Ghead at the posterior end of the operculum; Gmax at the maximum body depth), with the total length were estimated for each species and for the groups formatted when Geye, Ghead and Gmax were plotted against total length for all the species combined.